CORE VALUE DALAM BUDAYA ORGANISASI RABBANI - Tita Melia Milyane; Siti Syarah; Windi Ayu (Dialektika, 2018)
The development of the fashion world is now reaching an impressive point, supported by the advancement of information technology that broadens knowledge about various kinds of fashion. Especially Muslim fashion trends are characterized by the development of the "hijabers" community, Muslim fashion stores such as Rabbani, Shafira, Zoya, and others. Even Muslim clothing sales are also growing through online media. Muslim fashion experiences development with more interesting and modern innovations, namely an idea, practice, or thing that is considered / felt new by individuals or groups of people. Muslim fashion innovation is also experiencing several stages of innovation such as an awareness of innovation, the desire to innovate, the decision to innovate, try innovation and adopt these innovations.